Sustainability objectives and their influence on modern company law - Quijano González, Jesús (2024)
The need to promote and protect general interests subject to increasing threats, for which the collaboration of companies is essential, is leading to a change in trend in the configuration of the purpose of commercial companies, especially larger ones. From the traditional conception of companies as manifestations of the right of association for economic purposes, among which the obtaining of profit and its distribution among the partners appeared as a natural purpose, there has been an evolution towards a way of understanding the social interest in combination with other interests, such as the protection of the environment, the promotion of human rights or the implementation of participatory, gender-balanced governance models with more effective accounting and management control methods.Historically, this approach has been followed by the definition of corporate social responsibility commitments, and more recently by the requirement to provide formalized non-financial information that would allow the assessment of these commitments. At present, ESG sustainability objectives (environment, social issues, governance) are practically an obligation that companies must assume, providing regular information on their level of involvement in promoting these objectives. European initiatives in the field of sustainability, as well as in due diligence and gender balance, are expressions of particular interest in this new approach.